Invasive Species as Rivals: Invasive Potential and Distribution Pattern of Xanthium strumarium L. - Rafi Ullah (8146836) (2022)
Xanthium strumarium L. is a globally successful invasive herb that has had significant negative ecological, economic and social impacts in many world regions. The present study was therefore conducted to evaluate the invasive potential and spatial distribution patterns of X. strumarium in heavily invaded plant communities of the semiarid regions of northern Pakistan. Investigations were based on data from 20 plants grown in the Herbarium at the University of Malakand, and from observations in 450 plots distributed across 45 stands representing habitats across Northern Province including open fields, hillocks and abandoned areas in both urban and rural areas. Multivariate analysis identified elevation, organic matter and organic carbon as the environmental variables most associated with communities invaded by X. strumarium. Increased soil silt was positively associated and available water was negatively associated with X. strumarium–invaded communities. These key environmental characteristics allowed us to identify four main associations: Group I: X. strumarium-C. sativa, Group II: X. strumarium-P. hysterophorus, Group III: X. strumarium-A. aspera and Group IV: X. strumarium-C. sativa. Other invasive species were observed, either exotic, such as P. hysterophorus, or indigenous, such as C. sativa and D. inoxia, often co-occurring and responding similarly to these factors. The results suggest that high temperature with drought stress could be a determinant of increasing population at lower elevations, whereas colder climates with adequate moisture are related to reduced populations at higher elevations, near the species’ upper range limits. It is recommend that the inclusion of appropriate, additional soil and climatic variables in species distribution models be implemented in order to better explain species’ ecological niches and help guide conservation and protection plans for native plant communities. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14127141 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.